Effect of Andaliman (Zanthoxylum Acanthopodium DC) Extracts on The Histological Display of Lewy Body in The Brain of Rotenone Induced Wistar Rats - Afina, Lubna; Halim, Binarwan; Chiuman, Linda; Anggraeni, Wenti; Rizki, Kartika Sari (The Islamic Education and Multiculturalism Foundation, 2024)
Dementia Lewy Body (DLB) is a form of dementia characterized by abnormal accumulation of α-synuclein protein in the brain, forming lewy bodies that damage the function of neurons and nervous system. This study aimed to evaluate the effect of andaliman fruit extract (Zanthoxylum Acanthopodium DC), which is rich in antioxidants, on the number of lewy bodies in the brain of rotenone-induced Wistar male rats. Histology analysis was performed to observe the number of lewy bodies in the brain. The results showed a significant decrease in the number of lewy bodies in the treatment group compared to the positive control group (p<0.05). Increasing the dose of andaliman extract was directly proportional to the decrease in the number of lewy bodies, with the highest dose (450 mg/kgBB) providing the best protective effect. These findings suggest that the antioxidant content in andaliman extract can neutralize the oxidative stress caused by rotenone, thus protecting neurons from damage. This study supports the development of andaliman extract as an alternative therapy to prevent or inhibit the progressivity of DLB.